Business plans kit for dummies - Peterson, Steven (Wiley, 2016)
When you're establishing, expanding, or re-energizing a business, the best place to start is writing your business plan. Not only does writing out your idea force you to think more clearly about what you want to do, it will also give the people you work with a defined road map as well. Business Plan Kit For Dummies